Harmonisation and Between-Country Differences of the Lifetime of Experiences Questionnaire in Older Adults - Ourry, Valentin; Marchant, Natalie L.; Schild, Ann-Katrin; Coll-Padros, Nina; Klimecki, Olga M.; Krolak-Salmon, Pierre; Goldet, Karine; Reyrolle, Leslie; Bachelet, Romain; Sannemann, Lena; Meiberth, Dix; Demnitz-King, Harriet; et al. (Frontiers in Aging Neuroscience, 2021)
BACKGROUND: The Lifetime of Experiences Questionnaire (LEQ) assesses complex mental activity across the life-course and has been associated with brain and cognitive health. The different education systems and occupation classifications across countries represent a challenge for international comparisons. The objectives of this study were fourfold: to adapt and harmonize the LEQ across four European countries, assess its validity across countries, explore its association with brain and cognition and begin to investigate between-country differences in life-course mental activities. METHOD: The LEQ was administered to 359 cognitively unimpaired older adults (mean age and education: 71.2, 13.2 years) from IMAP and EU-funded Medit-Ageing projects. Education systems, classification of occupations and scoring guidelines were adapted to allow comparisons between France, Germany, Spain and United Kingdom. We assessed the LEQ’s (i) concurrent validity with a similar instrument (cognitive activities questionnaire - CAQ) and its structural validity by testing the factors’ structure across countries, (ii) we investigated its association with cognition and neuroimaging and (iii) compared its scores between countries. RESULTS: The LEQ showed moderate to strong positive associations with the CAQ and revealed a stable multidimensional structure across countries that was similar to the original LEQ. The LEQ was positively associated with global cognition. Between-country differences were observed in leisure activities across the life-course. CONCLUSIONS: The LEQ is a promising tool for assessing the multidimensional construct of cognitive reserve and can be used to measure socio-behavioural determinants of cognitive reserve in older adults across countries. Longitudinal studies are warranted to test further its clinical utility.